Effect of Bending of Carbon Dioxide Laser Fibers on Power Output. Issue 3 (16th July 2022) - Michaelides, Elias; Patel, Tirth R.
Abstract : Objective: The power output from carbon dioxide (CO2 ) laser fibers has the potential to be diminished if there are any bends along its course, which may alter the effect the laser has on the target tissue. In this study, we assess how bending of CO2 laser flexible fiber assemblies affects the energy output measured at the end of the fiber. Study Design: Laboratory study. Setting: Laboratory. Methods: Eight separate flexible fibers were tested—4 were of a type commonly used in endoscopic airway procedures, and the other 4 were a type used in otologic surgery. Fibers were bent in various configurations, and the power output of a CO2 laser fired through the bent fiber was measured. The output through the bent fiber was normalized to the output with a straight fiber. Correlations between bend parameters and power outputs was tested using Spearman's correlation coefficient. Results: For the airway fibers, there was a weak trend toward increasing energy outputs with greater radius of curvature ( P =. 714) and a negative correlation between the energy output and arc of rotation ( P =. 043). For the otologic fibers, there was a trend toward increasing energy outputs with greater radius ( P =. 084) and a strong negative correlation between the energy output and the arc of rotation ( P =. 006). Conclusion: CO2 laser energy output is reduced by bending of the laser fiber assembly. When using the CO2 laser fiber, surgeons should be aware of any bends in the fiber and are encouraged to take measures to minimize bending.